Mgl2+ cDC2s coordinate fungal allergic airway type 2, but not type 17, inflammation in mice - Peter C. Cook; Sheila L. Brown; Emma L. Houlder; Julio Furlong-Silva; Daniel P. Conn; Stefano A. P. Colombo; Syed Baker; Freya R. Svedberg; Gareth Howell; Margherita Bertuzzi; Louis Boon; Joanne E. Konkel; et al. (Nature Communications)
Abstract Fungal spores are abundant in the environment and a major cause of asthma. Originally characterised as a type 2 inflammatory disease, allergic airway inflammation that underpins asthma can also involve type 17 inflammation, which can exacerbate disease causing failure of treatments tailored to inhibit type 2 factors. However, the mechanisms that determine the host response to fungi, which can trigger both type 2 and type 17 inflammation in allergic airway disease, remain unclear. Here we find that CD11c+ DCs and CD4+ T cells are essential for development of both type 2 and type 17 airway inflammation in mice repeatedly exposed to inhaled spores. Single cell RNA-sequencing with further multi-parameter cytometry shows that allergic inflammation dramatically alters the proportion of numerous DC clusters in the lung, but that only two of these (Mgl2+ cDC2s and CCR7+ DCs) migrate to the dLNs. Targeted removal of several DC subsets shows that Mgl2+ cDC2 depletion reduces type 2, but not type 17, fungal allergic airway inflammation. These data highlight distinct DC subsets as potential therapeutic targets for the treatment of pulmonary fungal disease.